Effective interventions to prevent youth vaping behaviours: a rapid review - Ana Paula Belon; Laura Nieuwendyk; Tasha Allen; Melissa Worrell; Candace I J Nykiforuk (BMJ Open)
Objective To identify effective policies and non-policy interventions preventing youth vaping behaviour initiation and assess their effectiveness by the level of intrusiveness and subpopulations.Design This systematic rapid review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources Searches on MEDLINE and APA-PsycINFO for studies published between January 2019 and November 2023.Eligibility criteria Observational, intervention or mixed-method studies and quantitative systematic reviews/meta-analyses measuring the impact of interventions on youth (6–18 years) who never vaped or who had experimentally vaped.Data extraction and synthesis A predesigned form was used to extract data. To classify interventions by levels of intrusiveness, we used the PLACE Research Lab Intervention Ladder Policy Analysis Framework. We applied PROGRESS-Plus (Place of residence, Race/ethnicity/culture/language, Occupation,Gender/sex, Religion, Education, Socioeconomic status, Social capital, and additional context-specific factors) for an equity analysis. Methodological quality was assessed using the Effective Public Health Practice Project Quality Assessment Tool.Results 20 studies were included: 45% were experiments or quasiexperiments, 85% reported data from the USA, 65% were non-policy interventions and 40% and 35% measured susceptibility and attitudes and behaviours related to vaping, respectively. Considering the level of intrusiveness, 45% of the studies provided information and 25% eliminated choices. Overall, the certainty of evidence was low. The effectiveness of interventions regarding their level of intrusiveness varied by each outcome. No clear pattern was found between the level of intrusiveness and intervention effectiveness, suggesting that overall, the studied interventions positively changed youth vaping behaviours. Some interventions had positive effects on multiple outcomes. Equity-related findings suggested that younger youth may be less responsive to the interventions. Recommendations for action are provided.Conclusions We suggest that combining multiple interventions targeting different levels of intrusiveness and outcomes may be more effective in preventing youth vaping behaviours. Also important is to tailor programmes to younger youth to better meet their needs.